2020
DOI: 10.3390/s20082248
|View full text |Cite
|
Sign up to set email alerts
|

NeuroVAD: Real-Time Voice Activity Detection from Non-Invasive Neuromagnetic Signals

Abstract: Neural speech decoding-driven brain-computer interface (BCI) or speech-BCI is a novel paradigm for exploring communication restoration for locked-in (fully paralyzed but aware) patients. Speech-BCIs aim to map a direct transformation from neural signals to text or speech, which has the potential for a higher communication rate than the current BCIs. Although recent progress has demonstrated the potential of speech-BCIs from either invasive or non-invasive neural signals, the majority of the systems developed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The classification was performed with a 5-fold cross-validation (CV) strategy using a 2 nd order polynomial kernel. The choice of this 2 nd order kernel was motivated from our prior work [ 45 ], [ 70 ] which found that this kernel performs optimally compared to other kernels (radial basis function (RBF), sigmoid, 3 rd and 4 th order polynomial) for this MEG data. C parameter tells the SVM optimization how much is needed to avoid misclassifying each training example.…”
Section: Decoding Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The classification was performed with a 5-fold cross-validation (CV) strategy using a 2 nd order polynomial kernel. The choice of this 2 nd order kernel was motivated from our prior work [ 45 ], [ 70 ] which found that this kernel performs optimally compared to other kernels (radial basis function (RBF), sigmoid, 3 rd and 4 th order polynomial) for this MEG data. C parameter tells the SVM optimization how much is needed to avoid misclassifying each training example.…”
Section: Decoding Methodsmentioning
confidence: 99%
“…The classification was performed with a 5-fold cross-validation (CV) strategy using a 2 nd order polynomial kernel. The choice of this 2 nd order kernel was motivated from our prior work [46], [71] which found that this kernel performs optimally compared to other FIGURE 3: Forward sensor selection algorithm: This stepwise selection algorithm selects the most optimal set of sensors starting from 1 to 50, one by one in each step. First, the algorithm selects the first optimal sensor (O 1 ) which results in best CV accuracy when the SVM was trained with each sensor as input for 196 times (total number of sensors = 196).…”
Section: B Classifiermentioning
confidence: 99%
See 2 more Smart Citations
“…Features are extracted from each class (normal, ASD, VSD). The SVM classifier is a widely applied method of classification for biomedical signals [ 62 , 63 , 64 , 65 ] due to its excellent generalization capability. It obtains the optimal separating hyperplane for class separation by converting input features to higher dimensions through some nonlinear mapping [ 66 ].…”
Section: Methodsmentioning
confidence: 99%